Burnout and Workplace Incivility Among Emergency Medical Services Practitioners: A Preliminary Report. (19th May 2023) - Lu, Dave W.; Shin, Jenny; Wan, Christopher; Rea, Thomas D.; Crowe, Remle P.; Meischke, Hendrika W.; Counts, Catherine R.
Abstract: Objective: Burnout has detrimental consequences for health care organizations, clinicians, and the quality of care that patients receive. Prior work suggests that workplace incivility (negative interpersonal acts) contributes to burnout. While workplace incivility is linked to EMS practitioner job dissatisfaction, absenteeism, and planned attrition, the relationship between workplace incivility and burnout has not been evaluated among EMS practitioners. This study aimed to characterize the prevalence and association of burnout and workplace incivility among EMS practitioners. Methods: A cross-sectional survey of EMS personnel in King County, Washington was performed in January to March of 2021 with burnout as the primary outcome and workplace incivility as a secondary outcome. Multivariable logistic regression was used to evaluate associations between outcomes and EMS practitioner factors that included age, sex, race/ethnicity, years of EMS experience, and current job role. Results: 835 completed surveys were received (response rate 25%). The prevalence of burnout was 39.2%. Women were more likely to have burnout than men (59.3% vs. 33.7%, aOR 2.2, 95% CI 1.3–3.7). Workplace incivility was experienced weekly by 32.1% of respondents, with women more likely to experience incivility compared to men (41.9% vs. 27.2%, aOR 2.0, 95% CI 1.2–3.3). Respondents who experienced frequent workplace incivility were more likely to have burnout than those who did not experience frequent incivility (61.9% vs. 38.1%, OR 4.0, 95% CI 3.0–5.5). Conclusions: The prevalence of burnout and workplace incivility were concerning among EMS practitioners, with women more likely to experience both compared to men. EMS practitioners who experienced frequent workplace incivility were also more likely to have burnout than those who did not experience frequent incivility.